Assessment of theatre shoe contamination in an orthopaedic theatre. Issue 3 (July 2018) - Clesham, K.; Ryan, P.R.; Murphy, C.G.
Summary: Prosthetic joint infection (PJI) is a devastating complication of arthroplasty. Numerous protocols reduce potential risk for PJI peri-operatively, but none exist for the management of theatre shoes. Our aim was to assess for bacteria known to cause prosthetic infection on theatre shoes. Forty theatre shoes were analysed; there were coagulase-negative staphylococci on 65% ( N  = 25), meticillin-susceptible Staphylococcus aureus on 40% ( N  = 16), and meticillin-resistant S. aureus on 25% ( N  = 10). Amount of blood spatter correlated poorly with microbial contamination. Shoes harbouring Gram-positive bacteria, including antibiotic-resistant strains, provide a potential route of transmission to the theatre environment.